Peran Ekonomi Kreatif Dalam Meningkatkan Pendapatan Masyarakat Melalui Usaha Keripik Talas di Desa Kelewae Kecamatan Boawae Kabupaten Nagekeo - Aplonia Mogi Wea; Sayful Amrin; Maria Kristina Ota (Ekspektasi: Jurnal Pendidikan Ekonomi, 2025)
This qualitative research aims to describe the role of the creative economy and its impact on community income through the taro chip business in Kelewae Village, Nagekeo Regency. Data were collected through interviews, observations, and documentation from subjects including the leader and members of Dasawisma Nuri, as well as the Village Head. Data analysis followed the Miles and Huberman model. The results indicate that the creative economy is functioning well and serves as a tangible implementation at the village level. This business has successfully increased community income, particularly for housewives, through direct involvement in production and marketing. The study suggests that business owners enhance product innovation and digital marketing. Furthermore, the village government is expected to provide maximum support, while future researchers are encouraged to expand studies into distribution and financial management aspects.